Influence of plant growth regulators on vegetative growth, sex expression and yield of summer bottle gourd - Moniruzzaman, M; Khatoon, R; Moniruzzaman, M; Qamruzzaman, AKM (Bangladesh Journal of Agricultural Research, 2020)
Field experiments on bottle gourd variety ‘BARI Lau -4’ were conducted at the Plant Physiology field of Horticulture Research Center, Bangladesh Agricultural Research Institute, Gazipur during two consecutive summer seasons of 2015 and 2016 to investigate the effect of plant growth regulators on growth, sex expression, yield and yield components of the crop. The experiment consisted of different concentrations of Gibberellic acid (GA3), Naphthalene acetic acid (NAA), Maleic hydrazide (MH) and single concentration of cycocel (CCC) viz., GA3 @ 10 ppm, GA3 @ 30 ppm, NAA @100 ppm, NAA @ 150 ppm, MH @ 50 ppm, MH @ 150 ppm and CCC @ 500 ppm along with distilled water considered as control. All growth regulators were sprayed to the seedlings at two-leaf stage and 4 days after the first spray. Growth regulator treatments had significant effect on primary branches/plant, node number of 1st male and female flower appearance, number of days to 1st male and female flower appearance, number of male and female flowers, sex ratio (male:female flower) number of fruits/plant, individual fruit weight and fruit yield. Spraying of MH @ 150 ppm gave the highest primary branches/plant (17.0 and 18.0 in first and 2nd year, respectively) and induced maximum female flowers (37.3 and 40.0 in first and 2nd year, respectively) at lower nodes followed by CCC @ 500 ppm (36.3) in the first year and MH @ 50 ppm (40.0) in the 2nd year. Application of MH @ 150 ppm caused early appearance of female flowers on the nearest node (from bottom). Application of MH @ 150 ppm gave the lower number of male flowers (81.7 and 96.0 in first and 2nd year, respectively) and the highest number of female flowers/plant, thereby producing lower male:female sex ratio (2.2 and 2.5 in first and 2nd year, respectively) and the maximum number of fruits/plant (12.0 and 14.0 in first and 2nd year, respectively). The maximum fruit weight/plant was obtained from the application of MH @ 150 ppm (29.3 and 35.8 in first and 2nd year, respectively) followed by CCC @ 500 ppm (26.0 in the 1st year and 29.0 in 2nd year). The highest fruit yield per hectare was recorded significantly with the application of MH @ 150 ppm (97.6 t/ha and 89.6 t/ha in first and 2nd year, respectively) closely followed by CCC @ 500 ppm (88.5 t/ha in 2015) and GA3 @ 30 ppm (75.3 t/ha in 2016), as compared to other treatments. The highest mean yield over the years was also recorded at MH @ 150 ppm (93.6 t/ha) followed by CCC @ 150 ppm (80.6 t/ha) and GA3 30 (74.1). Application of MH @ 150 ppm gave the maximum gross return and net return with the highest BCR of 5.24 followed by CCC 500 ppm (4.15) and GA3 30 ppm (3.86). Bangladesh J. Agril. Res. 44(4): 577-590, December 2019